The missing step in proving the equivalence of \( 12a + 10 + a = 10 + a + 12a \) using the Commutative Property is:
Step 1: 12a + 10 + a = 10 + 12a + a
This step simply rearranges the terms on the left side of the equation.
So the complete proof would look like this:
- \( 12a + 10 + a = 10 + 12a + a \) (using the Commutative Property)
- \( 10 + 13a = 10 + 13a \) (by combining like terms)
- The expressions are equivalent because they both equal the same value.
Therefore, the correct response is: 12a + 10 = 10 + 12a.